Expansion of Imaginal Disc Growth Factor Gene Family in Diptera Reflects the Evolution of Novel Functions - Zurovcova, Martina; Benes, Vladimir; Zurovec, Michal; Kucerova, Lucie (Insects, 2019)
Imaginal disc growth factors (IDGFs) are a small protein family found in insects. They are related to chitinases and implicated in multiple functions, including cell growth stimulation, antimicrobial activity, insect hemolymph clotting, and maintenance of the extracellular matrix. A number of new IDGFs have been found in several insect species and their detailed phylogenetic analysis provides a good basis for further functional studies. To achieve this goal, we sequenced Idgf cDNAs from several lepidopteran and trichopteran species and supplemented our data with sequences retrieved from public databases. A comparison of Idgf genes in different species showed that Diptera typically contain several Idgf paralogs with a simple exon-intron structure (2-3 exons), whereas lepidopteran Idgfs appear as a single copy per genome and contain a higher number of exons (around 9). Our results show that, while lepidopteran Idgfs, having single orthologs, are characterized by low divergence and stronger purifying selection over most of the molecule, the duplicated Idgf genes in Diptera, Idgf1 and Idgf4, exhibit signs of positive selection. This characterization of IDGF evolution provides, to our knowledge, the first information on the changes that formed these important molecules.
Keywords: chitinase; chitinase-like protein; Drosophila; phylogeny; IDGF; positive selection